The Kid - Hansen, Ron 1947- (Scribner, 2016)
"A new novel from Ron Hansen, the award-winning author of The Assassination of Jesse James by the Coward Robert Ford, about an iconic American criminal of the old West: legendary outlaw, Billy the Kid. Born Henry McCarty, Billy the Kid was a diminutive, charming, blond-haired young man who, growing up in New York, Kansas, and later New Mexico, demonstrated a precocious dexterity at firing six-shooters with either hand...a skill that both got him into and out of trouble and that turned him into an American legend of the old West. He was smart, well-spoken, attractive to both white and Mexican women, a good dancer, and a man with a nose for money, horses, and trouble. His spree of crimes and murders has been immortalized in dime westerns, novels, and movies. But the whole story of his short, epically violent life has never been told as it has been here. In The Kid, Ron Hansen showcases his masterful research and inimitable style as he breathes life into history, bringing readers back into the late 1800s and into Billy's boyhood as a ranch hand just trying to wrest a fortune from an unforgiving landscape. We are with Billy in every gunfight and horse theft and get to know him in full before his grand death in a hail of bullets in 1881 at the age of twenty-one. Original, powerful, and swiftly told, The Kid is an unforgettable read about a uniquely American anti-hero"...